A Rustling in The Overstory: More-Than-Human Storytelling in Richard Powers’s Novel - Austin, Patrycja (Sensus Historiae, 2020)
This paper analyses the way Richard Powers portrays plant life in his 2018 novel The Overstory. Unlike in traditional literary depictions of botany, trees are presented as actors and not passive objects. By undermining the mind/ matter, human/ nonhuman distinctions Powers reduces the gap separating his human protagonists and trees. The latter have agency, intentionality and the ability to communicate. Powers also attempts to find a new way to give his vegetal life voice. Instead of anthropomorphizing them, plants talk in their own material way. This paper draws from posthumanist writings by, among others, Donna Haraway Anna Tsing Lowenhaupt, Mark Jackson, Maria Puig de la Bellacasa, and also from Michael Marder’s and Serpil Opperman’s ideas on plant language and storytelling.